The concept of maqomat in the journey of human life - Abdillah, Nur Muhammad (Maliki Interdisciplinary Journal, 2024)
Maqamat in the context of this journal refers to spiritual concepts in the journey of human life. This journal abstract discusses the importance of maqamat in understanding the spiritual journey and human self-development.This journal describes maqamat as stages in the human spiritual journey that aims to achieve closeness to God. These stages involve inner transformation and increased self-awareness through life experiences.The journal writer explains that every individual has the potential to reach a higher maqamat in his life's journey. However, attaining this maqamat requires deep self-awareness, spiritual discipline, and sustained effort.This journal also describes the characteristics of maqamat which include sincerity, fortitude, humility, and sensitivity to God's presence in every aspect of life. Maqamat is also seen as a source of inspiration and motivation for self-improvement and achieving the highest spiritual potential lJournal authors provide concrete examples of how individuals who reach certain levels in their life's journey experience positive changes in attitudes, behavior, and relationships with the surrounding environment.